Shaping medieval markets : the organisation of commodity markets in Holland, c. 1200-c. 1450 - Dijkman, Jessica (Global economic history series, 2011)
In the late Middle Ages the county of Holland experienced a process of uncommonly rapid commercialisation. Comparing Holland to England and Flanders this book examines how the institutions that shaped commodity markets contributed to this remarkable development.